KETERAMPILAN DAN KESEJAHTERAAN FINANSIAL SUBJEKTIF PADA MAHASISWA: PERAN LITERASI KEUANGAN DIGITAL - Rachmaniar Myrianda Dwiputri; Muhammad Kausar Maulana (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2024)
The issue of financial well-being among university students is increasingly receiving attention from researchers. The aim of this research is to examine the relationship between financial skills and subjective financial well-being in students. In addition, this study examines the mediating role of digital financial literacy on the relationship between these two variables. The data collected is then processed using structured equation modelling. The findings of this study indicate a positive relationship between financial skills and subjective financial well-being. Digital financial literacy was also found to mediate the relationship between financial skills and subjective financial well-being. This research contributes to giving color to the science of human behavior, in the field of finance in particular, by including the digital financial literacy variable as a mediating variable for the relationship between financial skills and subjective financial well-being. In addition, these findings have the implication that financial digital literacy in students is an important factor that will improve their subjective financial well-being.